2008
DOI: 10.2113/gsecongeo.103.6.1243
|View full text |Cite
|
Sign up to set email alerts
|

Synvolcanic and Younger Plutonic Rocks from the Blake River Group: Implications for Regional Metallogenesis

Abstract: The Blake River Group of the Abitibi greenstone belt is host to the well-known volcanogenic massive sulfide (VMS) deposits of the Noranda camp, Québec, Canada. In the Noranda camp massive sulfide deposits are spatially associated with the coeval Flavrian-Powell intrusive complex, which is interpreted to have driven hydrothermal circulation that formed the deposits in the camp. In the western Blake River Group in Ontario there are also abundant intrusive rocks, yet relatively insignificant accumulations of VMS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 102 publications
1
11
0
Order By: Relevance
“…Most of these deposits that formed in the upper few kilometers of crust, before ca. 20 to 30 Ma, have been uplifted and eroded and thus lost from the geologic record (Groves et al, 2005a), although there are a few significant exceptions dating back through the Mesozoic (e.g., Ling et al, 2009), Paleozoic (e.g., Khashgerel et al, 2009), and even to the Late (Piercey et al, 2008a) and Early Archean (Harris et al, 2009). The secular distribution of orogenic gold, which correlates with periods of supercontinent growth ( Fig.…”
Section: Secular Variation Of Mineral Depositsmentioning
confidence: 99%
“…Most of these deposits that formed in the upper few kilometers of crust, before ca. 20 to 30 Ma, have been uplifted and eroded and thus lost from the geologic record (Groves et al, 2005a), although there are a few significant exceptions dating back through the Mesozoic (e.g., Ling et al, 2009), Paleozoic (e.g., Khashgerel et al, 2009), and even to the Late (Piercey et al, 2008a) and Early Archean (Harris et al, 2009). The secular distribution of orogenic gold, which correlates with periods of supercontinent growth ( Fig.…”
Section: Secular Variation Of Mineral Depositsmentioning
confidence: 99%
“…8-11). Two main models have been proposed to explain the genesis of TTG suites in modern and ancient settings: (i) slab-melting of subducted oceanic crust and (or) (ii) the delamination and hydrous melting of Pagination not final (cite DOI) / Pagination provisoire (citer le DOI) stacked and thickened mafic crust (Drummond and Defant 1990;Drummond et al 1996;Martin 1999;Martin and Moyen 2002;Martin et al 2005;Bedard 2006;Jiang et al 2007;Wang et al 2007;Smithies 2000;Piercey et al 2008;Wyman and Kerrich 2009;Moyen 2009). In the case of the slab melt model, workers have suggested that slab-melts would have reacted with the mantle wedge resulting in TTG-like rocks with enrichments in MgO, Cr, and Ni (e.g., Defant and Drummond 1990;Martin et al 2005;Rapp et al 1999;Bedard 2006;Richards and Kerrich 2007).…”
Section: Petrogenesis Of the Porcupine Intrusive Suitesmentioning
confidence: 99%
“…The absence of MgO, Cr, and Ni enrichments in the TIS argue against slab meltmantle wedge interactions and a slab melt model for their origin (e.g., Martin et al 2005;Rapp et al 1999;Bedard 2006;Richards and Kerrich 2007). In contrast, the melting of mafic crust related to delamination of stacked and thickened basaltic crust, with garnet and hornblende stable in the restite, best explains the geochemistry of the TIS suite (e.g., Rapp et al 1991;Feng and Kerrich 1992;Wyllie et al 1997;Rapp 1997;Moyen and Stevens 2006;Piercey et al 2008;Beakhouse 2011). This is also consistent with the geological evolution of the Timmins region.…”
Section: Petrogenesis Of the Porcupine Intrusive Suitesmentioning
confidence: 99%
See 1 more Smart Citation
“…The distribution of the elements and elemental ratios in these plots define the corresponding compositional fields: pink corresponds to felsic, light green to mafic, light blue to ultramafic, light purple to lamprophyre and the dashed field to intermediate rocks. Data used to define the fields are from the following sources: Arndt and Nesbitt, 1982;Arndt, 1986;Barrie et al, 1991aBarrie et al, , b, 1999Beswick, 1983;Canil, 1987;Dinel et al, 2008;Dostal and Muller, 2013;Fan and Kerrich, 1997;Feng and Kerrich, 1992;Finamore et al, 2008;Fralick et al, 2009;Gaboury and Pearson, 2008;Goldstein and Francis, 2008;Hollings and Wyman, 1999;Hollings and Kerrich, 1999a, b;Hollings and Kerrich, 2000;Innes, 1978;Kerrich et al, 1999Kerrich et al, , 2008Kitayama and Francis, 2014;Lafrance et al, 2000;Lahaye et al, 1995;Lahaye and Arndt, 1996;Maurice et al, 2003Maurice et al, , 2009Merci-Langevin et al, 2007;Nesbitt et al, 2009;Parks et al, 2014;Picard and Piboule, 1986;Piercey et al, 2008;Polat et al, 1999Polat et al, , 2012Polat and Kerrich, 1999;Pollat and Münker, 2004;Pollat, 2009;Rinne and Hollings, 2013;Sproule ...…”
Section: Acknowledgmentsmentioning
confidence: 99%